Continuous Erector Spinae Plane and Intrathecal Opioid Analgesia: Novel Regimen Avoiding Thoracic Epidural Analgesia and Systemic Morphine in Open Radical Cystectomy. Issue 6 (15th March 2019) - Warusawitharana, Chinthaka; Tariq, Zubair; Jackson, Benjamin; Niraj, G.
Abstract : There has been a significant shift away from epidural analgesia after radical cystectomy within an enhanced recovery program. Alternative techniques reported including continuous erector spinae plane analgesia require supplemental systemic morphine. A new analgesic regimen is described that avoids both thoracic epidural analgesia and systemic morphine. Three adult patients undergoing open radical cystectomy, who refused thoracic epidural analgesia, were offered continuous erector spinae plane and intrathecal opioid analgesia. Median length of hospital stay was reduced by a third. The novel analgesic regimen may have the potential to enhance recovery after open radical cystectomy.